The bone marrow of mouse-rat chimeras contains progenitors of multiple pulmonary cell lineages - Li, Enhong; Wen, Bingqiang; Gao, Dengfeng; Kalin, Timothy R.; Wang, Guolun; Kalin, Tanya V.; Kalinichenko, Vladimir V. (Frontiers in Cell and Developmental Biology, 2024)
Radiation-induced lung injury (RILI) is a common complication of anti-cancer treatments for thoracic and hematologic malignancies. Bone marrow (BM) transplantation restores hematopoietic cell lineages in cancer patients. However, it is ineffective in improving lung repair after RILI due to the paucity of respiratory progenitors in BM transplants. In the present study, we used blastocyst injection to create mouse-rat chimeras, these are artificial animals in which BM is enriched with mouse-derived progenitor cells. FACS-sorted mouse BM cells from mouse-rat chimeras were transplanted into lethally irradiated syngeneic mice, and the contribution of donor cells to the lung tissue was examined using immunostaining and flow cytometry. Donor BM cells provided long-term contributions to all lung-resident hematopoietic cells which includes alveolar macrophages and dendritic cells. Surprisingly, donor BM cells also contributed up to 8% in pulmonary endothelial cells and stromal cells after RILI. To identify respiratory progenitors in donor BM, we performed single-cell RNA sequencing (scRNAseq). Compared to normal mouse BM, increased numbers of hematopoietic progenitors were found in the BM of mouse-rat chimeras. We also identified unique populations of hemangioblast-like progenitor cells expressing Hes1, Dntt and Ebf1, along with mesenchymal stromal cells expressing Cpox, Blvrb and Ermap that were absent or ultra-rare in the normal mouse BM. In summary, by using rats as “bioreactors”, we created a unique mouse BM cell transplant that contributes to multiple respiratory cell types after RILI. Interspecies chimeras have promise for future generations of BM transplants enriched in respiratory progenitor cells.